Using facebook for the purpose of students interaction and its correlation with students academic performance - Al Dheleai, Y. M. (Sakarya University, 2017)
Facebook has now become the most popular social networking tool among university-aged youth. Its popularity has transformed it into an acceptable platform for educational purposes. The use of Facebook is currently more suited to facilitate online interaction among learning participants. The purpose of this study is to investigate students’ perception towards the use of Facebook for course-related online interaction and its effect on academic performance. The data were collected using a survey method of data collection. A quantitative data analysis process was employed using SPSS statistics software. The findings of the study revealed that students had positive views towards the use of Facebook for online interaction with peers. Additionally, the findings reveal that there is a relationship between students’ perceived online interaction via Facebook and academic performance.